2019
DOI: 10.1371/journal.pone.0208913
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori infection increases risk of incident metabolic syndrome and diabetes: A cohort study

Abstract: Emerging studies have shed light on the association between Helicobacter pylori (HP) infection and cardiometabolic risk. However, there is no evidence to support a causal link for the relationship in the general population. Our aim was to determine whether HP infection is associated with the risks of incident type II diabetes mellitus (DM) in a population-based cohort consisting of adults from the general population. A total of 69235 adults enrolled in the study obtained health examinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
1
22
1
2
Order By: Relevance
“…Among 13 autoimmune diseases evidence in support of a probable role of HPI was found in four—TP, Graves’ disease, neuromyelitis optica and psoriasis [ 361 ]. Just to mention some examples of contradictory conclusions: many reports and meta-analyses suggested a positive correlation between HPI, metabolic associated fatty liver disease (MAFLD; previous term non-alcoholic fatty liver disease, NAFLD) [ 362 , 363 , 364 , 365 , 366 , 367 , 368 , 369 , 370 , 371 , 372 ], type 2 diabetes mellitus (DM)/insulin resistance [ 373 , 374 , 375 , 376 , 377 ], diabetic complications [ 378 , 379 , 380 ] and obesity [ 381 , 382 ], whereas others did not found such associations [ 383 , 384 , 385 , 386 , 387 , 388 , 389 ] and some described an inverse correlation of HPI with obesity [ 390 , 391 , 392 ]. Similarly, there is discrepancy between various studies regarding links between HPI and cardiovascular diseases (CVD) [ 333 , 393 , 394 , 395 , 396 , 397 , 398 , 399 , 400 ].…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…Among 13 autoimmune diseases evidence in support of a probable role of HPI was found in four—TP, Graves’ disease, neuromyelitis optica and psoriasis [ 361 ]. Just to mention some examples of contradictory conclusions: many reports and meta-analyses suggested a positive correlation between HPI, metabolic associated fatty liver disease (MAFLD; previous term non-alcoholic fatty liver disease, NAFLD) [ 362 , 363 , 364 , 365 , 366 , 367 , 368 , 369 , 370 , 371 , 372 ], type 2 diabetes mellitus (DM)/insulin resistance [ 373 , 374 , 375 , 376 , 377 ], diabetic complications [ 378 , 379 , 380 ] and obesity [ 381 , 382 ], whereas others did not found such associations [ 383 , 384 , 385 , 386 , 387 , 388 , 389 ] and some described an inverse correlation of HPI with obesity [ 390 , 391 , 392 ]. Similarly, there is discrepancy between various studies regarding links between HPI and cardiovascular diseases (CVD) [ 333 , 393 , 394 , 395 , 396 , 397 , 398 , 399 , 400 ].…”
Section: Hpi-associated Chronic Extra-gastroduodenal Diseases Medmentioning
confidence: 99%
“…Several studies supported our results on the lack of association between H. pylori infection and diabetes [ 17 , 20 , 26 ]. In contrast, others found H. pylori infection to be positively associated with diabetes [ 19 , 21 , 27 , 28 ]. A meta-analysis that included 41 case-control studies concluded that H. pylori infection could be a potential risk factor for type 2 diabetes, while among them, two studies conducted in China both showed a negative result [ 29 ].…”
Section: Discussionmentioning
confidence: 94%
“…Chen et al examined the correlation between H pylori and MeS, showing a positive association (OR 1.26; CI 95%: 1.00‐1.57) only in males. A positive association was also found with T2DM (OR 1.59; CI 95%: 1.17‐2.17), especially in patients with duodenal ulcer (HR 1.63; CI 95%: 1.02‐2.63) rather than those with gastroesophageal reflux disease (GERD) or gastric ulcer . Alshareef et al described a positive association between H pylori infection and gestational diabetes (OR 2.8: CI 95%: 1.1‐7.5; P < .036) and insulin resistance in Sudanese women, while Kato et al tested 21 634 patients for active or past‐ H pylori infection and presence of DM and reported an association between current H pylori infection and increased risk of DM, which disappeared after eradication .…”
Section: Metabolic Syndrome and Diabetes Mellitusmentioning
confidence: 97%